The Influence of Using Online Oxford Dictionary Toward Pronunciation and Vocabulary Mastery - Wulansari, Tika Wulansari; Fakhrurriana, Ria (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2024)
In order to clearly express the ideas, students need to master pronunciation and have vast vocabulary. Media and strategy are essential matter to achieve well-acquired vocabulary and good pronunciation. Online dictionary such as Oxford Advanced Learners’ Dictionary (later abbreviated as OALD) is one of the media to aid students in improving pronunciation and vocabulary. Students used to utilize the book version of OALD, yet, nowadays they prefer to use the online form through internet networking. Thus, this research aims to determine the influence of using online Oxford Dictionary on students’ pronunciation and vocabulary at the fourth students of English Department of State Islamic Institute of Kediri (IAIN Kediri). 30 students of English Education study program were chosen as the subject of this qualitative study. This research used questionnaire and interview to collect the data related to an alternative reference in technology for learning vocabulary and pronunciation especially online Oxford Dictionary. The results of the questionnaire were processed descriptively. The research results showed that the online Oxford Dictionary influence students’ pronunciation and vocabulary enrichment. It is recommended to solve the problem of pronunciation and vocabulary mastery.